Implikasi Person Job-Fit Terhadap Komitmen Karir Dengan Keterlibatan Kerja Sebagai Variabel Intervening - Kurnia, Efelyne; Kornelius, Yoberth; Idris; Islianty, Nur Riski (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the effect of person–job fit on career commitment, with work engagement as an intervening variable among 52 Agricultural Quarantine Center employees. Data were analyzed using PLS-SEM. The findings show that person–job fit has a positive and significant effect on career commitment and work engagement. Work engagement also positively and significantly affects career commitment and significantly mediates the relationship between person–job fit and career commitment. This study implies that organizations should improve human resource quality through appropriate job placement and stronger employee work engagement. Keywords: Person–Job Fit; Work Engagement; Career Commitment